The correlation of 25-Hydroxyvitamin D (25-(OH)D) to IgE level, eosinophil, and Asthma Control Test (ACT) score in asthma patients - Ery Olivianto; Ade Habibi; Muchammad Fahrul Udin; HMS Chandra Kusuma (Pediatric Sciences Journal, 2022)
Background: Asthma is a heterogenouse disease with chronic inflammation which is characterized by hyperreactivity and obstruction of respiratory tract. Many hypothesis of asthma were related with nutrition, such as vitamin D status. Vitamin D is a precursor of steroid hormone that has immunomodulator effect but the relationship of asthma and vitamin D still controversial. This study aims to find the relationship of vitamin D (25-(OH)D) with level of IgE, Eosinophils, and asthma control test (ACT) in mild to moderate pediatric asthmatic patient. Method: An observational analytic study with cross-sectional approach has been conducted among 40 pediatric asthmatic patients by consecutive sampling technique. Data regarding gender, age, vitamin D status, the levels of 25-(OH)D, IgE, Eosinophil, and ACT score were assessed in this study. Correlation analysis test was used as statistical analysis using SPSS version 20 for Windows.Result: Most of respondents were male (70.0%), 5-7 years of age range (52.5%), and insufficient of vitamin D (20-30 ng/ml) (45.0%). The recent study suggests a significant negative relationship between serum 25 (OH) D levels with total immunolobulin E levels (p=0.002; r=-0.476) and eosinophils (p = 0.002; r=-0.479). However, the 25-(OH)D level did not show a significant relationship with the ACT score (p = 0.195; r=0.209).Conclusion: Negative relationship was found between total serum 25(OH)D, total immunoglobulin E, and eosinophils in children with asthma. Moreover, 25(OH)D was not related to ACT score in children with asthma.